EFFECTS OF PERFORMANCE CONTRACTING ON EMPLOYEES’ PERFORMANCE IN COMMERCIAL BANKS: A CASE OF FAMILY BANK WESTERN REGION BRANCHES, KENYA - WANJIKU, NGUGI MARY; WANYONYI, Dr. KADIAN WANYAMA; SIALO, MR. FELIX; SANGORO, MR. OSCAR (IJRDO - Journal of Business Management, 2016)
The objective of performance contracting is the control and enhancement of employees’performance and thus the performance of the whole institution. Performance contracting is a freelynegotiated performance agreement between the employers and employees. It is the latest strategyused in the banking sector to enhance employee’s performance. The purpose of the study was toassess influence of performance contracting effect on employees’ performance in Family Bank.The study employed a descriptive research design. The study targeted 301 employees from 15branches of Family Bank in Western region, from which a sample size of 45 respondents wasobtained. Stratified random sampling and simple random sampling were used. The researchinstruments used included both closed-ended questionnaire and focus group discussion besides theinterview schedules. Results revealed positive and significant associations between setting ofperformance targets, monitoring and evaluation, performance contracting process andimplementation of performance contracting on employee performance in Family Bank branchesin Western region of Kenya.